Home range and movement patterns of selected vertebrates (Zoological Records and Reviews, 2024)
Understanding home range size and movement behaviour in vertebrates is fundamental to wildlife management, corridor design, and predicting responses to habitat fragmentation. This study quantified home range area, daily displacement, and habitat selection for five vertebrate species--three mammals (Capreolus capreolus, Vulpes vulpes, Mustela putorius) and two reptiles (Lacerta agilis, Natrix natrix)--across contrasting landscape contexts in northern Italy and central Switzerland between March 2021 and November 2023 (n = 124 individuals tracked). GPS-GSM collars and passive integrated transponder (PIT) telemetry were deployed for mammals and reptiles, respectively. Home ranges were estimated using fixed-kernel density estimation (KDE95) and minimum convex polygons (MCP100). Mean KDE95 home range areas differed significantly among species (Kruskal-Wallis H = 84.3, p < 0.001): Vulpes vulpes exhibited the largest ranges (mean 14.7 +- 3.2 km2), followed by Capreolus capreolus (4.8 +- 1.1 km2) and Mustela putorius (1.9 +- 0.6 km2).Lacerta agilis and Natrix natrix maintained ranges of 0.018 +- 0.004 ha and 0.31 +- 0.09 ha, respectively. Habitatselection analyses (compositional analysis and Resource Selection Functions) revealed strong preference forwoodland-edge ecotones across all five species. Landscape fragmentation index (splitting index > 3.4) was negativelycorrelated with Capreolus capreolus home range size (r = -0.61, p < 0.001), indicating range compression in degradedlandscapes. These results provide empirical baseline data for species-specific corridor width recommendations andinform land-use planning in peri-urban agricultural mosaics of central Europe.
Keywords: central Europe; resource selection function; landscape fragmentation; movement ecology; Vulpes vulpes; Capreolus capreolus; habitat selection; GPS telemetry; kernel density estimation; home range